The Role for the Small Cryptic Plasmids As Moldable Vectors for Genetic Innovation in Aeromonas salmonicida subsp. salmonicida - Attéré, Sabrina A.; Vincent, Antony T.; Paccaud, Mégane; Frenette, Michel; Charette, Steve J. (Frontiers in Genetics, 2017)
In Aeromonas salmonicida subsp. salmonicida, a bacterium that causes fish disease, there are two types of small plasmids (<15 kbp): plasmids without known function, called cryptic plasmids, and plasmids that bear beneficial genes for the bacterium. Four among them are frequently detected in strains of A. salmonicida subsp. salmonicida: pAsa1, pAsa2, pAsa3 and pAsal1. The latter harbors a gene which codes for an effector of the type three secretion system, while the three others are cryptic. It is currently unclear why these cryptic plasmids are so highly conserved throughout strains of A. salmonicida subsp. salmonicida. In this study, three small plasmids, named pAsa10, pAsaXI and pAsaXII, are described. Linked to tetracycline resistance, a partial Tn1721 occupies half of pAsa10. A whole Tn1721 is also present in pAsa8, another plasmid previously described in A. salmonicida subsp. salmonicida. The backbone of pAsa10 has no relation with other plasmids described in this bacterium. However, the pAsaXI and pAsaXII plasmids are derivatives of cryptic plasmids pAsa3 and pAsa2, respectively. pAsaXI is identical to pAsa3, but bears a transposon with a gene that encodes for a putative virulence factor. pAsaXII, also found in Aeromonas bivalvium, has a 95% nucleotide identity with the backbone of pAsa2. Like pAsa7, another pAsa2-like plasmid recently described, orf2 and orf3 are missing and are replaced in pAsaXII by genes that encode a formaldehyde detoxification system. These new observations suggest that transposons and particularly Tn1721 are frequent and diversified in A. salmonicida subsp. salmonicida. Moreover, the discovery of pAsaXI and pAsaXII expands the group of small plasmids that are derived from cryptic plasmids and have a function. Although their precise roles remain to be determined, the present study shows that cryptic plasmids could serve as moldable vectors to acquire mobile elements such as transposons. Consequently, they could act as key agents of the diversification of virulence and adaptive traits of Aeromonas salmonicida subsp. salmonicida.